Ameliorating effects of herbal formula hemomine on experimental subacute hemorrhagic anemia in rats. (23rd February 2017) - Ku, Sae Kwang; Kim, Hyemee; Kim, Joo Wan; Kang, Ki Sung; Lee, Hae-Jeung
Abstract: Ethnopharmacological relevance: Hemomine (HM) is an herbal mixture consisting of 5 varieties of the hematopoietic herbal extracts ( Angelica gigas Nakai, Cnidium officinale Makino, Paeonia lactiflora Pall., Rehmannia glutinosa Liboschitz ex Stueudel, Glycyrrhiza uralensis Fischer). Aim of the study: Anemia has been treated with iron supplements, whereas it could cause adverse side effects such as digestive discomfort. In the present study, HM was applied to SHA rats to test for several activities so as to verify its therapeutic potentials on anemia and digestive discomfort. Materials and methods: Sprague-Dawley rats were assigned to seven groups: (Two controls, two references (ferric hydroxide polymatose (FM) and ferritin extract glycerin hydrate (FA)), three different concentrations of HM, n=8 per groups), and induced subacute hemorrhagic anemia (SHA) through blood exsanguinations once a day for 7 days. Results: The SHA animal model showed changes in the markers related to classic iron-deficient and regenerative anemia in this experiment. However, the SHA related anemic signs were dose-dependently inhibited by the administration of HM 2, 1, and 0.5 ml/kg for 7 days, and more favorably than the equal dosages of FM and FA. In addition, FM and FA showed the typical constipation signs, including reduction of in thickness of the colonic mucosa, in contrast, HM 2, 1, and 0.5 ml/kg groups had no effects on the gastrointestinal motilities and the colonic mucous components when compared to the controls. The results suggested that the HM significantly showed to have therapeutic effects in the experimental SHA in rats, and is more potent than the commercial iron supplement through the proliferation of hematopoietic stem cells with reduced digestive discomfort. Conclusions: Therefore, Hemomine may prove to be a promising hematopoietic and therapeutic agent for anemia. Graphical abstract: